2015
DOI: 10.4314/jasem.v19i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Stem Bark Extracts of <i>Ficus exasperata</i> protects the Liver against Paracetamol induced toxicity in Wistar Rats

Abstract: ABSTRACT:Ficus exasperata is an important medicinal plant with a wide geographical distribution in Africa particularly in Nigeria. In this study, aqueous stem bark extracts of Ficus exasperata were administered to investigate its hepatoprotective effects on Paracetamol induced liver toxicity in Wistar rats. A total of Twenty Five Wistar rats were randomly divided into five groups labeled A-E and kept in a well ventilated room. Group A served as control and were treated with distilled water. Rats in groups B-E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…SV for 21 days and paracetamol in the last 4 days resulted in a significant increase in serum AST, ALT, ALP, and total bilirubin levels and significant decrease in serum albumin and total protein levels associated with significant increase in liver MDA, TNF‐α, Caspase‐3 and significant decreased liver SOD, GPx, and GSH. These results are in agreement with Knight et al., Uzkeser et al., Hassanin et al., Alantary et al., and Enogieru et al . who found that paracetamol resulted in elevation of liver enzymes and increased MDA level, lipid peroxidation, and elevation of TNF‐α.…”
Section: Discussionsupporting
confidence: 92%
“…SV for 21 days and paracetamol in the last 4 days resulted in a significant increase in serum AST, ALT, ALP, and total bilirubin levels and significant decrease in serum albumin and total protein levels associated with significant increase in liver MDA, TNF‐α, Caspase‐3 and significant decreased liver SOD, GPx, and GSH. These results are in agreement with Knight et al., Uzkeser et al., Hassanin et al., Alantary et al., and Enogieru et al . who found that paracetamol resulted in elevation of liver enzymes and increased MDA level, lipid peroxidation, and elevation of TNF‐α.…”
Section: Discussionsupporting
confidence: 92%
“…The roots are also used to manage asthma (14). Studies have confirmed veracity of some of these local uses, including antimicrobial activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella typhi and Klebsiella pneumonia (15), anti-arthritic and anti-oxidant effects (11), and hepatoprotective effects of its aqueous extract (16). The study is aimed at adding to the body of evidence of the anti-salmonellal activity of F. exasperata.…”
Section: Introductionmentioning
confidence: 93%
“…Innov. 2(6) 49-56, 2023 Momoh et al, 2018, Bigoniya and Singh, 2014, Ezzat et al, 2020, Okroro, 2018, Ajiboyea et al, 2018, Ashraf et al, 2018, Chinala et al, 2018, Lee et al, 2017, Enogieru et al, 2015, Abbas et al, 2017, Shyama et al, 2020, Zahra et al, 2012, Akbari et al, 2019, Akbarizare et al, 2021, Ezzat et al, 2020, Lee et al, 2017, Choudhary et al, 2014, Ghareeb et al, 2019, Elmansi et al, 2017, Acheampong et al, 2021 Paracetamol/ Acetaminophen Azadirachta indica, Phyllanthus niruri, Phyllanthus emblica, Phyllanthus niruri, V. amygdalina, Taraxcum officinale, Zingibar officinale, Solanum torvum, Allium sativum, Allium cepa, Moringa oleifera, Momordica charantia, Calotropis procera, Juniperus communis, Hibiscus sabdariffa, Hibiscus cannabinus, Clerodendron inerme, Parkia biglobosa, Saponaria officinalis, Solanum indicum, Maytenus emerginata, Eclipta alba, Aloe vera, Aegle mameloes, Spathodea campanulate, Ficus exasperata Ezzat et al, 2020, Momoh et al, 2015, Usmani et al, 2019, Ige et al, 2017, Iwo et al, 2017, Koubaa et al, 2020, Kermani et al, 2020, Farghali et al, 2015, Mahdi et al, 2019, Momoh et al, 2018, Muhammad et al, 2014, Moracles-Gonzalez, 2014 Azadirachta indica, Phyllanthus amarus V. amygalina, Curcuma longa, Phyllanthus niruri, Syz ygium aromaticum, Moringa o...…”
Section: Toxicants Challenged With the Plant Speciesmentioning
confidence: 99%